Analysis of Code Mixing in Social Media - Nur Putri Lianda; Lismalinda Lismalinda; Budi Rizka (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
The development of current language causes most people, including youtubers, often mix the language in their conversation, for example in Indonesian to English. The purpose of this study was to determine the use of code mixing between Deddy Corbuzier and Jerome Polin. This study examines code mixing that occurs in the YouTube Podcast dialogue. Data collection is done by writing a code-mixing dialogue and then marking words or phrases or sentences in the dialogue. The results showed that most of youtubers used code-mixing in their conversations because they mixed Indonesian and English to communicate. This research method is a qualitative descriptive method. The object of this research is code mixing used by Deddy and Polin in a podcast. Based on these findings, the researcher concludes that Deddy and Polin used three of two types of code mixing, namely insertion, and alternation. This is evident through of the observation and research that the English used by youtubers produces a lot of substitutions and the reasons of code mixing through of speaker and partner, participant roles and relationships, desire to explain something situational. The results also showed that they used code mixing in their dialogue as an expression of their group speaking.